Influence of the machining cooling strategies on the dental tribocorrosion behaviour of wrought and additive manufactured Ti6Al4V. (September 2017) - Bertolini, R.; Bruschi, S.; Ghiotti, A.; Pezzato, L.; Dabalà, M.
Highlights: Tribocorrosion behaviour of dry, wet and cryogenic machined Ti6Al4V were studied. Wear tests in a wet and temperature-controlled apparatus were performed. Improved in-vitro behaviour characterized cryogenic machined Ti6Al4V cylinders. EBM emerged as suitable route for manufacturing biomedical implants. Lower volume of wear characterized the cryogenic machined Ti6Al4V pins.